Sistem Kendali Navigasi Ar.Drone Quadcopter Dengan Prinsip Natural User Interface Menggunakan Microsoft Kinect - Sabitha Wildani Hadi; Gembong Edhi Setyawan; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Quadcopter is a type of Unmanned Aerial Vehicle (UAV), which is a robot that can fly with fourpropellers. Quadcopter can controlled with remote control or smartphone, but it takes skill andexperience to be able to control quadcopter. Based on that problems, it is necessary to develop newinnovation of quadcopter navigation control system which is easier to use. The system built on thisresearch is made using one part of the natural user interface that is user's body gestures detected usingKinect. User's gestures will be converted into sceleton tracking. The sceleton tracking data will beprocessed by computer with javascript programming and will be forwarded into instructions to controlquadcopter. Quadcopter used in this research is Parrot AR.Drone 2.0. After performing test on thesystem, obtained percentage of accuracy of user's gestures to control quadcopter is 100%. In addition,the results obtained from the speed test of roll, pitch, and yaw on the quadcopter is directly proportionalto the input value of the user's gestures which means the speed of the quadcopter can be adjustedautomatically according to the user's gestures. For the delay on this system when the user moves thebody until the quadcopter follows the instruction is 0.05 seconds.